2022
DOI: 10.1101/2022.08.24.505165
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Schizophrenia-associatedNRXN1deletions induce developmental-timing- and cell-type-specific vulnerabilities in human brain organoids

Abstract: De novo mutations and copy number variations (CNVs) in NRXN1 (2p16.3) pose a significant risk for schizophrenia (SCZ). How NRXN1 CNVs impact cortical development in a cell type-specific manner and how disease genetic background modulates these phenotypes are unclear. Here, we leveraged human pluripotent stem cell-derived brain organoid models carrying NRXN1 heterozygous deletions in isogenic and SCZ patient genetic backgrounds and conducted single cell transcriptomic analysis over the course of cortical brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 119 publications
0
2
0
Order By: Relevance
“…4D). Though we observed a minor position variability in their neural activity, all three positions showed robust synchronous and spontaneous firing with expected metrics as previously published 60 . Hence, our results show free floating MIBOs that were cultured long-term out of the device yield active and viable organoids with mature neural network characteristics.…”
Section: Characterizing the Functioning Neural Circuits In Mibos Usin...supporting
confidence: 87%
“…4D). Though we observed a minor position variability in their neural activity, all three positions showed robust synchronous and spontaneous firing with expected metrics as previously published 60 . Hence, our results show free floating MIBOs that were cultured long-term out of the device yield active and viable organoids with mature neural network characteristics.…”
Section: Characterizing the Functioning Neural Circuits In Mibos Usin...supporting
confidence: 87%
“…The gene expression values for these genes from our previous RNA-seq study ( Brocato and Wolstenholme, 2023 ) are shown in Supplementary Figure S4 . Specifically, Kcnh7 , Nrxn1 and Cntn5 have been associated with myelin formation or phenotypes ( Boscia et al, 2021 ; Dauar et al, 2022 ; Sebastian et al, 2022 ), and glutamate signaling has been shown to be important to oligodendrocyte development and survival ( Kougioumtzidou et al, 2017 ; Turan et al, 2021 ). Changes to the regulation of these genes and others involved in synaptic function could impact the progression of oligodendrocyte maturation and play a role in ethanol-induced myelin reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Neurexin 1 (NRXN1) deletions are linked to increased risk in schizophrenia. Along with cell-specific transcriptional changes, organoids with NRXN1 deletions displayed decreased synchronized calcium burst activity at 4-5 months of culture compared to control organoids (Sebastian et al, 2023). Network oscillations have also been found to be altered in organoids subject to different pressure shockwaves modeling primary blast injury.…”
Section: Astrocyte Coordination Of Neural Network Activity Within Org...mentioning
confidence: 97%